Estudio piloto: necesidades energéticas de mujeres en edad fértil con actividad agrícola en el distrito de Campoverde, provincia Coronel Portillo, departamento de Ucayali, Perú, comparadas con las recomendaciones internacionales de la FAO/OMS/UNU de 2004 - Ruth Beatriz Quiliche Castañeda (2019)
Objective: To estimate the percentage of adaptation of the energy expense measured with the techniqueof the monitoreo of heart frequency regarding the effective international energy recommendations s deof the FAO / OMS / UNU 2004 in women in fertile age with agricultural activity of four villages of thedistrict of Campoverde, province Coronel Portillo, department Ucayali, Peru.Method: Traverse and analytic study. It was carried out in the villages - The Winners, The Pines,Good Grass and twenty-three October of the district of Campoverde during December of 2005 to Januaryof 2006.Of 102 women in fertile age that they were visited in their housing 61 (59,81%) they qualified, theyaccepted and they committed to participate in the study.Results: The average of the estimated energy necessities according to the equations of the FAO / OMS/ UNU 2004 was 2 047,66 ± 192,11; 2 372,73 ± 288,16; y 2 304,22 ± 298,41 calories versus the expense energytotal measured with the technique of the monitoreo of heart frequency that was: 2 785,00 ± 108,28; 2 622,19± 478,62; y 2 518,67 ± 397,41 for the groups of 10,00 to 17,99 years, 18,00 at 29,99 years and 30,00 to 59,99years respectively with statistical significance in the three age groups p <0.05.Conclusions: The energy expense measured through the technique of the monitoreo of heart frequencycompared with the effective international energy recommendations according to the FAO / OMS /UNU 2004 in women in fertile age was bigger in the three groups etáreos.